Variations in attack behaviours between Glossina palpalis gambiensis and G-tachinoides in a gallery forest suggest host specificity - (:unkn) unknown (My University, 2016)
Tsetse flies Glossina palpalis gambiensis and G. tachinoides are among the major vectors of sleeping sickness (Human African Trypanosomiasis-HAT) and nagana (African Animal Trypanosomiasis-AAT) in West Africa. Both riparian species occur sympatrically in gallery forests of south west Burkina Faso, but little is known of their interspecies relationships although different authors think there may be some competition between them. The aim of this study was to check if sympatric species have different strategies when approaching a host. A man placed in a sticky cube (1mx1mx1m) and a sticky black-blue-black target (1mx1m) were used to capture tsetse along the Comoe river banks in a Latin Square design. The number and the height at which tsetse were caught by each capture method were recorded according to species and sex. Glossina p. gambiensis was more attracted to human bait than to the target, but both species were captured at a significantly higher height on the target compared with the human bait (P<0.05). No significant difference in heights was found between G. tachinoides and G. p. gambiensis captured on targets (33 and 35cm, respectively, P>0.05). However, catches on human bait showed a significant difference in height between G. tachinoides and G. p. gambiensis (22.5 and 30.6cm, respectively, P<0.001). This study showed that these sympatric species had different attack behaviours to humans, which is not the case with the target. The implications of these findings are discussed.
Keywords: African Research